2019
DOI: 10.1016/j.parkreldis.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of unilateral deep brain stimulation on voice tremor in patients with essential tremor

Abstract: Voice tremor (VT) is a common symptom of Essential tremor (ET). Deep brain stimulation (DBS) is an established treatment for ET overall, however, its effect on VT is less clear. The aim of this study was to evaluate long-term effects of DBS on VT and to investigate how VT symptoms develop over time in patients with ET. Methods: VT scores for the cohort of 81 ET patients that had undergone DBS surgery in the caudal zona incerta (cZi) were analyzed retrospectively. Thirty-four patients had preoperative VT and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…For the long-term pre versus postimplantation analyses, 6 studies ( n = 165) with Vim stimulation [12, 17, 18, 20, 30, 31] and 5 studies ( n = 86) with PSA stimulation [26, 27, 32, 33] met inclusion criteria. The weighted average follow-up times were 36.3 months and 38.6 months, respectively, for Vim and PSA stimulation groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the long-term pre versus postimplantation analyses, 6 studies ( n = 165) with Vim stimulation [12, 17, 18, 20, 30, 31] and 5 studies ( n = 86) with PSA stimulation [26, 27, 32, 33] met inclusion criteria. The weighted average follow-up times were 36.3 months and 38.6 months, respectively, for Vim and PSA stimulation groups.…”
Section: Resultsmentioning
confidence: 99%
“…1). At short-term follow-up, 10 studies (n = 300) with Vim stimulation [13,[17][18][19][20][21][22][23][24][25] and 9 studies (n = 200) with PSA stimulation [7,10,12,13,[26][27][28][29] met inclusion criteria for preimplantation versus postimplantation analyses. The weighted average follow-up times were 9.96 months and 11.3 months, respectively, for Vim and PSA stimulation groups.…”
Section: Patient Demographics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cZi is a small nucleus targeted in-between the red nucleus (Rn) and the posterior tip of the STN (pSTN) at the depth where the Rn has its maximal diameter (see Figure 1; Blomstedt, 2018), and this has been the DBS target of choice for ET at Umeå University Hospital since 2004. Previous investigations into the effects of DBS in the cZi have shown that unilateral cZi DBS can have a positive effect on voice tremor (Sandström et al, 2019b(Sandström et al, , 2018, also in the long term (Sandström et al, 2019a), and that habitual cZi DBS, optimized to treat the motor symptoms of ET, does not affect speech intelligibility (Sandström et al, 2020). However, in the same clinical population, it was also noted that speech intelligibility might deteriorate during highamplitude stimulation from electrode contacts higher up in the PSA (Sandström et al, 2020) and that successful voice tremor management may depend on the exact location of the electrode within the cZi (Sandström et al, 2019b); results that indicate that speech and voice outcomes could vary depending on targeting precision.…”
mentioning
confidence: 99%
“…Voice tremor is also a common symptom of ET that can interfere with communication and adversely affect quality of life (Chandran & Pal, 2013;Louis & Gerbin, 2013). While voice tremor may improve with DBS (Avecillas-Chasin et al, 2019;Hägglund et al, 2016;Matsumoto et al, 2016;Sandström et al, 2018Sandström et al, , 2019, stimulation-induced dysarthria is a frequently reported adverse effect, especially in those treated bilaterally (Alomar et al, 2017). DBS has been found to cause imprecise articulation and a slow speech rate (Mücke et al, 2014(Mücke et al, , 2018Plaha et al, 2011) in persons with ET and induce symptoms that can generally be described as characteristic of ataxic or mixed ataxic-spastic dysarthria (Matsumoto et al, 2016), but with "preserved intelligibility" (Matsumoto et al, 2016;Plaha et al, 2011).…”
mentioning
confidence: 99%